The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4257/oeco.2016.2002.06
|View full text |Cite
|
Sign up to set email alerts
|

Composition, Body-Size Structure and Biomass of Zooplankton in a High-Elevation Temporary Pond (Minas Gerais, Brazil)

Abstract: Small ponds are vital inland water bodies, recognized as small repositories of freshwater biodiversity, but neglected in terms of conservation. Although high-elevation ponds are difficult to sample and monitor, it is important to extend their study, in view of their importance to aquatic biodiversity. The aim of this study was to analyze the composition, size structure biomass and diversity of zooplankton community in a temporary pond (Lagoa Seca) of a low-alpine area in the southern part of Serra do Espinhaço… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 42 publications
(47 reference statements)
1
6
0
1
Order By: Relevance
“…Other studies in Brazilian aquatic ecosystems recorded much higher zooplankton species richness both in temporary and in perennial environments (reservoirs and rivers). Passos (2012) found 20 to 23 taxa in three shallow temporary ponds in the municipality of Urucuia, Minas Gerais (near to the ponds of this study); Passos (2017) registered 68 taxa for a total of 25 shallow temporary ponds from Minas Gerais (municipalities of Urucuia, Lagoa Grande and Pirapora) studied during three consecutives years (2015 to 2017); Moreira et al (2016) registered 29 taxa in a shallow high-elevation temporary pond in Minas Gerais; in São Paulo State, Melão (1997) found 28 taxa in a shallow permanent oligotrophic reservoir and Santos (2010) found richness ranging from 17 to 36 in three large big reservoirs of Tietê River (São Paulo); Silva (2015), in a review of studies done in large amazonic rivers, reported 143 species in the Madeira River and 129 species in the Xingu River. It is possible, however, that our results underestimate the real richness of zooplankton species in the studied ponds, since we did a single sampling campaign and resistance eggs of the species from such temporary ecosystems can hatch in different times (Passos, 2017).…”
Section: Taxonomic Diversity and Biomassmentioning
confidence: 51%
“…Other studies in Brazilian aquatic ecosystems recorded much higher zooplankton species richness both in temporary and in perennial environments (reservoirs and rivers). Passos (2012) found 20 to 23 taxa in three shallow temporary ponds in the municipality of Urucuia, Minas Gerais (near to the ponds of this study); Passos (2017) registered 68 taxa for a total of 25 shallow temporary ponds from Minas Gerais (municipalities of Urucuia, Lagoa Grande and Pirapora) studied during three consecutives years (2015 to 2017); Moreira et al (2016) registered 29 taxa in a shallow high-elevation temporary pond in Minas Gerais; in São Paulo State, Melão (1997) found 28 taxa in a shallow permanent oligotrophic reservoir and Santos (2010) found richness ranging from 17 to 36 in three large big reservoirs of Tietê River (São Paulo); Silva (2015), in a review of studies done in large amazonic rivers, reported 143 species in the Madeira River and 129 species in the Xingu River. It is possible, however, that our results underestimate the real richness of zooplankton species in the studied ponds, since we did a single sampling campaign and resistance eggs of the species from such temporary ecosystems can hatch in different times (Passos, 2017).…”
Section: Taxonomic Diversity and Biomassmentioning
confidence: 51%
“…Each female produced a mean of 10 ± 3.46 broods during its life cycle. After egg production halted, females survived for 2.5 ± 0.98 days, usually abundant in shallow lakes (Moreira et al, 2016). Their abundance can be associated with the close relationship with the dense presence of aquatic vegetation (Bolduc et al, 2016), since they are specialized in exploiting microenvironments provided by vegetation (Scheffer, 2004;Forró et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The pond is an oligotrophic, slightly acid seasonal aquatic water body, with mean value of pH below 6.5 and mean annual water temperature of 19 °C. (Moreira et al, 2016). Samples were obtained in January 2014 by filtration of 30 L of water in a 68 µm mesh size plankton net.…”
Section: Methodsmentioning
confidence: 99%
“…The lakes were classified in two categories according to water fluctuation: permanent or temporary (lake that dry at least once a year). To determine these categories (permanent or temporary), data from previous studies of the lakes (Moreira et al 2015;Moreira et al 2016) and information provided by the management of the Conservation Units were used. The values (lake area, altitude, macrophyte cover) and categories (permanent and temporary) were applied in the multivariate analyses (PERMANOVA) as an independent variable to explain the variations in the richness of zooplankton species.…”
Section: Sampling Procedures Of Zooplankton and Environmental Variablesmentioning
confidence: 99%